A longitudinal study of information systems research in Australia - Pervan, Graham; Shanks, G. (ANU ePress, 2008)
This paper reports a longitudinal study that explores the state of Information Systems (IS) research in Australia. A series of surveys was distributed to the heads of all IS discipline groups in Australian universities in 2004, 2005 and 2006. The study highlights the current state of IS research in Australia from the 2006 survey and analyses the trends in IS research over the last few years. The study revealed a wide range of topics researched (with rapid growth in Electronic Commerce and Knowledge Management), a range of foci, a balance between positivist and interpretivist research, survey was the most frequently used research method, and most research was directed at informing IS professionals. A SWOT analysis identified the growing importance of industry relevance and collaboration. Research performance, measured by publication output and research grant income, is shown to be improving, but is dominated by universities from the Sandstone/Redbrick and Unitech sectors, and overall does not compare favourably with other disciplines.